Meningkatkan Kemampuan Berpikir Kreatif Melalui Model PBL Berbantuan Media Gambar Ilustrasi Pada Pembelajaran IPAS Kelas IV SD - Bunalan Murtala, Windi Putri Lestari; Putra, Deni Adi; Naila , Ishmatun (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Muhammadiyah Sukabumi, 2024)
This research aims to describe the implementation of the PBL model with the help of illustration media. Describe the increase in creative thinking skills after implementing the PBL model. This type of research, classroom action research (CAR). The subject of this research aims to improve creative thinking skills in science and social learning using the PBL model with the help of illustrative image media. The target students are 16 people and come from class 4th Grade of SD Muhammadiyah 18 Surabaya, there are 7 girls and 9 boys in this class. The research was conducted in the odd semester of 2023. Data collection techniques such as observation and tests were used to collect data for this research. Based on the results, there have been changes and improvements in students’ creative thinking from the first cycle, 6 students (37.5%) were very creative, there were 10 students (62.5%) who were not creative, whereas in the second cycle there had been a lot of improvement, there were 15 students (93.75%) who were very creative and only 1 student (6.25%) who was not creative, in connection with the above, we can say that: 4th grade students of SD Muhammadiyah 18 Surabaya benefit from implementing the PBL model in their science and social learning, this shows that 4th grade students of SD Muhammadiyah 18 Surabaya gain increased creative thinking skills when they study science and social.